Aksi Bersih Pantai Paradiso sebagai Upaya Peningkatan Kesadaran Lingkungan Masyarakat di Kota Kupang - Frenly Marvi Selanno; Meilyn Renny Pathibang; Jeriels Matatula; Flora Evalina Ina Kleruk; Fransiskus X Dako; Nusrah Rusadi; Kletus Florianus Sera Gare; Sukriati Andesti Lamanda (Universitas Mataram, 2026)
This community service activity aims to increase public environmental awareness through a beach cleanup activity at Paradiso Beach, Kupang City. The main problem faced is the high amount of waste in coastal areas, especially inorganic waste in the form of plastic that can pollute the environment and disrupt the coastal ecosystem. The activity was carried out on July 7, 2025, by the Forestry Department of the Kupang State Agricultural Polytechnic through a beach cleanup and environmental education for the community and tourists. The implementation method was carried out in three stages: preparation, implementation, and post-implementation. The results of the activity showed the collection of 757 kg of inorganic waste and 56 kg of organic waste. The high amount of inorganic waste indicates that plastic waste is still a major problem in coastal areas. This activity has a positive impact on increasing public awareness of beach cleanliness and creating a cleaner and more comfortable coastal environment. Thus, beach cleanup activities need to be carried out sustainably through collaboration between the community, government, and educational institutions to support coastal environmental conservation.